0507 Prevalence, Sleep Characteristics, And Comorbidity Of High Risk For Obstructive Sleep Apnea: A Nationwide Questionnaire Study In South Korea. (27th April 2018) - Yang, K; Sunwoo, J; Hwangbo, Y; Kim, W; Chu, M; Yun, C
Abstract: Introduction: Clinical questionnaires can be a convenient and efficient means of screening individuals at high risk of obstructive sleep apnea (OSA). The Berlin questionnaire is the most widely used questionnaire for screening for a high risk of OSA in clinical practice and its screening properties have been validated in several population-based studies. We determined the prevalence, associated factors, and health consequences of a high risk for OSA in the Korean adult population. Methods: We analyzed data from 2, 740 subjects who responded to a nationwide questionnaire survey of sleep characteristics. Those who qualified under two or more symptom categories of the Berlin questionnaire were defined as "at high risk for OSA". We investigated their socio-demographic information, sleep habits, and medical and psychiatric comorbidities. Logistic regression analyses were performed to identify factors and consequences significantly associated with a high risk for OSA. Results: The prevalence of a high risk for OSA was 15.8% (95% confidence interval [CI] 14.5–17.2%). Multiple logistic regression analysis showed that old age (≥ 70 years, odds ratio [OR] 2.68) and body mass index ≥ 25 kg/m 2 (OR 10.75) were significantly related with a high risk for OSA, whereas regular physical activity (OR 0.70) had a protective effect. Subjective sleep characteristics associated with a high risk for OSA were perceived insufficient sleep (OR 1.49), excessive daytime sleepiness (OR 1.88), and insomnia (OR 3.70). In addition, hypertension (OR 5.83), diabetes mellitus (OR 2.54), hyperlipidemia (OR 2.85), and anxiety (OR 1.63) were comorbid conditions independently associated with a high risk for OSA. Conclusion: This is the first study to demonstrate the prevalence of a high risk for OSA in a nationwide representative sample of the Korean adult population. These findings elucidate the epidemiology and clinical characteristics of those at high risk for OSA. Support (If Any):